PENGARUH NON PERFORMING FINANCING (NPF), INFLASI, DAN DANA PIHAK KETIGA (DPK) TERHADAP TINGKAT PEMBIAYAAN MURABAHAH PADA BANK SYARIAH MANDIRI - Amilliya Virdina Rezza Setyo Ningrum; Nanik Kustiningsih (LPPM Universitas Bina Bangsa, 2023)
Sharia Bank is a sharia-based financial institution that is currently in the process of refinement, innovation and continuous efforts in the development process due to the high potential of the sharia economy in Indonesia. Focusing on the long-term effects of Islamic banking ready to face turbulent economic conditions. The writing of this article is motivated by the phenomenon that occurs in Bank Syariah Mandiri (BSM) from annual financial report data for the period 2012 to 2018. In this study, researchers used quantitative methods and the type of data used was secondary data. The sample used in this study is the annual financial report of Bank Syariah Mandiri for the 2012-2018 period which includes the NPF, TPF, Murabahah and BI inflation reports for the 2012-2018 period. The data analysis technique used in this research is descriptive statistics, classical assumption test, multiple linear regression with a significance level of 5% hypothesis testing. The results of this study were processed using the SPSS Version 22 for Windows program